Investigating the Methods of Management in Education with Taking the Case of a Teacher at the Stage of University - Tulina, Ekaterina V. (2020)
The paper reveals the problem of the professional formation of a future teacher, training a teacher with a high intellectual level of self-awareness, being capable of conceptual thinking, creativity and being ready to independently managing one’s own professional activity, which will allow interacting more effectively with the learning environment, being an active subject of professional and pedagogical activity.